(untitled) (Asian Education Studies, 2017)
Internet users have given two existing phrases in Chinese, “Jiang Zhen” and “Lao Siji” new second definitions. “Jiang Zhen” which exists in some southern Chinese dialects is gradually becoming a new Mandarin phrase. The phrase’s meaning is being transformed and this new meaning is being used by Chinese netizens. This new and transformed meaning has spread quickly throughout the internet. On the other hand, “Lao Siji” now has several new meanings and has become more popular in online and real life conversations. From the three dimensions of language namely semantics, syntax and pragmatics, the two new phrases have their intrinsic connotations. Currently, different sections of the public hold different attitudes to these two new phrases, so their vitality is still waiting for the test of time.